Badnaviruses and banana genomes: a long association sheds light on Musa phylogeny and origin. (24th November 2020) - Chabannes, Matthieu; Gabriel, Marc; Aksa, Abderrahmane; Galzi, Serge; Dufayard, Jean‐François; Iskra‐Caruana, Marie‐Line; Muller, Emmanuelle
Abstract: Badnaviruses are double‐stranded DNA pararetroviruses of the family Caulimoviridae . Badnaviral sequences found in banana are distributed over three main clades of the genus Badnavirus and exhibit wide genetic diversity. Interestingly, the nuclear genome of many plants, including banana, is invaded by numerous badnaviral sequences although badnaviruses do not require an integration step to replicate, unlike animal retroviruses. Here, we confirm that banana streak viruses (BSVs) are restricted to clades 1 and 3. We also show that only BSVs from clade 3 encompassing East African viral species are not integrated into Musa genomes, unlike BSVs from clade 1. Finally, we demonstrate that sequences from clade 2 are definitively integrated into Musa genomes with no evidence of episomal counterparts; all are phylogenetically distant from BSVs known to date. Using different molecular approaches, we dissected the coevolution between badnaviral sequences of clade 2 and banana by comparing badnavirus integration patterns across a banana sampling representing major Musa speciation events. Our data suggest that primary viral integrations occurred millions of years ago in banana genomes under different possible scenarios. Endogenous badnaviral sequences can be used as powerful markers to better characterize the Musa phylogeny, narrowing down the likely geographical origin of the Musa ancestor. Abstract : Banana‐related badnavirus sequences have undergone different coevolution processes with their host plant over the time, with some of them being either integrated or episomal while others are both integrated and episomal.